Investigating the antecedents of customer online repurchase intention in a multichannel environment - Rizwan, Muhammad (2020)
The evolution of internet technology, rapid digitalization, and the introduction of multiple channels strongly influence the managers and researchers to discover and update how customers better interact in a multichannel environment. Therefore, in today’s multichannel environment, the question of whether multiple channels should be implemented is no longer the focus. More important is the question of how the multiple channels can be handled synergistically to maximize the customer repeat purchase behavior. The current quantitative study attempts to understand whether the role of channel integration helps in customer movement from the firm’s offline channel to the firm’s online channel. Data have been collected from a sample of 358 experienced online customers from different cities of Pakistan and analyzed through smart PLS. The results of the study confirm that the customer previous interaction with the firm offline channel significantly affects the customer perception about the firm’s online channel. Additionally, the results of the study also confirm the moderating role of channel integration and offline image in the transfer of customer perceptions form offline channel to online channel. Although each channel may offer a unique value proposition, channel integration can drive overall customer satisfaction and repeat purchase behavior in a relational, multichannel environment. Therefore, it is pertinent for the firms and managers to not only focus on their new online channel but also their performance in the offline channel to provide a better purchase experience for the customers across multiple channels. Moreover, integrating multiple channels can provide a synergy that helps the firms to achieve competitive advantage.